LEVERAGING GENERATIVE AI FOR SUSTAINABLE DIGITAL EMPOWERMENT IN INDIGENOUS COMMUNITIES - Srivastava, Sankalp; Upadhyay, Dr. Parijat (PUPIL: International Journal of Teaching, Education and Learning, 2024)
In an endeavour to tackle global inequality through digitalization, this study concentrates on utilizing the capabilities of Generative Artificial Intelligence (Generative AI) to empower Indigenous communities. The aim of this research is to investigate how Generative AI can mitigate socio-economic disparities by safeguarding indigenous knowledge and promoting social justice, all while being conscious of the historical biases faced by these communities. By employing innovative research tools that leverage Generative AI, the researchers delve into its applications within Indigenous contexts in India. Their findings underscore the potential of Generative AI in advancing cultural preservation, strengthening social cohesion, and establishing sustainable economic opportunities. This research sheds light on a transformative path toward digital empowerment and social justice for marginalized Indigenous communities